EVALUASI KINERJA PERUSAHAAN DAERAH BANK PENGKREDITAN RAKYAT - Rahman, Abdul (Jurnal Ilmu Administrasi Negara, 2016)
Regional Company Performance Evaluation rural credit banks. This study aims to determine the performance of Regional Company of rural credit banks Rokan Hulu, Rokan Hulu Regency. Quantitative descriptive research type with the number of respondents totaled 50 people sampled in the study. The data analysis is based on the Balanced Scorecard method consisting of perspective, financial perspective and the customer (customer). The results showed that the performance Rokan Hulu PD BPR based financial perspective shows a good performance, because of the five aspects assessed, three aspects showed a good performance. Meanwhile PD BPR performance Rokan Hulu is based on the customer’s perspective shows good performance because three of the five aspects assessed increased and showed a good performance.